(3QSGdI aj GdQHGs - (3YHO GdYRjR Hf QGTOs
(3ChdgG (B:s
(3GdMeO ddg GdgGOi Edi SHjd GdQTGO hHYO cfJ CXf Cf jaJi GdTjN eMehO TdJhJ HMd ahGFO UfOhb GdHQjO s
(3BNQgG (B:s
(3hYf LGHQ bGd bGd QShd Gddg Udi Gddg Ydjg hSde dYf Gddg Bcd GdQHG hehcdg hcGJHg hTGgOjg hbGd ge ShGA QhGg eSde s
(3HgG fXGe GdJYbjHIs
(3cJHJ Hbde MOjKs
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9334) s
Keywords: (3CUhd Gdabgs